Synchronization of Sputum Conversion and Resolution of Intensive Phase Lesion Areas on Thorax X-rays Determinants of Prognosis for Pulmonary Tuberculosis Therapy - Ambarsari, Utami; Arimbi, Muzaijadah Retno; Veterini, Lysa; Indrianto, Yunita Lestari; Candini, Naura Anindya; Notobroto, Hari Basuki (Jurnal Ilmu Kesehatan dan Kesehatan, 2023)
Background: Pulmonary tuberculosis (TB) is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis. Diagnosis of TB can be confirmed in two ways, namely bacteriological diagnosis (if AFB sputum is found (+) and clinical diagnosis is (if BTA sputum is found (-), but chest X-ray is (+) TB). Objective: to determine the alignment of sputum conversion and extensive resolution of intensive phase lesions on chest radiographs which determine the prognosis of pulmonary TB therapy. Methods: The study design was a retrospective cohort analytic with a retrospective longitudinal study design. Data from medical records of pulmonary TB patients who have undergone therapy for six months or more at the Pulmonary Polyclinic RSI Jemursari Surabaya. The number of samples was 48 patients aged 41-60 years. All of these pulmonary TB patients were smear positive (BTA+). X-ray examination was done before and after therapy. Results: analysis using the Wilcoxon Signed Rank test to assess differences in the grade of lung lesions before and after therapy, obtained p = 0.003 (p <0.05) meaning there is a significant difference. Sputum conversion was also carried out after therapy, 89.6% of TB patients in this study experienced sputum conversion (BTA negative). To determine the alignment of sputum conversion with the resolution of lesion area, Kappa coefficient analysis K=0.033 (p>0.05) was performed with the results of 50% of patients, 47.9% showed improvement in lung lesions and sputum conversion, while 2.1% showed no improvement of lung lesions and no sputum conversion. The rest, 50% showed no congruence in the results of lung lesion repair and sputum conversion. Conclusion: The results of Kappa coefficient analysis showed that K=-0.110 (p>0.05) showed that there was no congruence between the results of chest x-ray examination of lung lesions before and after therapy (improved or not) with sputum conversion